Frauenarbeit in Freien Exportzonen: Eine Übersicht - Wick, Ingeborg (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1998)
The article gives a review of the existing export processing zones all over the world. The biggest part of the labor force of such zones are young women, who work under bad conditions. Wages are low and usually trade unions are suppressed.